Adverse pregnancy outcomes associated with antiretroviral therapy initiated before pregnancy and during pregnancy: a retrospective study in Hubei province, China - Tan, Yuting; Wu, Songjie; Yan, Yajun; Zou, Shi; Feng, Ling; Guo, Wei; Wu, Mengmeng; Luo, Mingqi; Liang, Ke (Frontiers in Medicine, 2023)
Background: Antiretroviral therapy (ART) initiation before pregnancy was reported to have an increased risk of adverse pregnancy outcomes (APOs) than ART initiation during pregnancy. However, the risks of APOs associated with different ART regimens initiated before or during pregnancy remain unknown. Methods: Pregnant women living with HIV (PWLHIV) from Hubei Province, China, were retrospectively enrolled between January 1, 2004, and December 31, 2021. The trends of ART initiation time and application of different ART regimens were evaluated over time, separately. Using no ART exposure before and during pregnancy as control, the risks of APOs associated with protease inhibitor (PI) based regimens and non-nucleoside reverse transcriptase inhibitors (NNRTIs) based regimens initiated before pregnancy were analyzed; and the risks of APOs associated with PI-based regimens, NNRTIs based regimens and zidovudine (AZT) monotherapy initiated during pregnancy were analyzed. APOs, including low birthweight (LBW), stillbirth, preterm birth (PTB) and early miscarriage, were reviewed. Results: Among 781 PWLHIV including 1010 pregnancies, 522 pregnancies (51.7%) were exposed to ART before or during pregnancy. Of them, the proportion of ART initiation before pregnancy per year increased from around 20% in the early period to more than 60% after 2019. Efavirenz (EFV)-nucleoside reverse transcriptase inhibitors (NRTIs) (32.2%), LPV/r-NRTIs (31.2%), and nevirapine (NVP)-NRTIs (27.4%) were the most commonly used regimens, and the proportion of LPV/r-NRTIs used per year has increased to around 50.0% in recent years. LPV/r-NRTIs was associated with higher risks of LBW whether initiated before pregnancy [adjusted OR (aOR)=2.59, 95%CI 1.04-6.45, p=0.041] or during pregnancy (aOR=2.19, 95%CI 1.03-4.67, p=0.041), compared with no exposure to ART before and during pregnancy. However, no matter initiated before or during pregnancy, LPV/r-NRTIs had no significantly increased risks of stillbirth, PTB and early miscarriage, and EFV /NVP-NRTIs and AZT monotherapy had no significantly increased risks of LBW, stillbirth, PTB and early miscarriage when compared with no exposure to ART before and during pregnancy. Conclusion: Our data suggests that LPV/r-NRTIs has been widely used among PWLHIV in recent years. However, the potential risk of LBW should be continuously monitored among PWLHIV whether LPV/r-NRTIs is initiated before or during pregnancy.